2015
DOI: 10.13189/ujms.2015.030101
|View full text |Cite
|
Sign up to set email alerts
|

Complexion Formation in PVA/PEO/CuCl<sub>2</sub> Solid Polymer Electrolyte

Abstract: Solid polymer electrolyte films based on polymer blends of poly(vinyl alcohol) (PVA) and poly(ethylene oxide) (PEO), with different concentration of copper (II) chloride (CuCl 2 ) were prepared using casting technique. Optical studies were performed using Fourier transform infrared (FT-IR) and Ultraviolet-visible (UV-Vis) spectroscopy. The optical properties of these films were varied by varying CuCl 2 concentration. The results show the absorption edge for electrolyte samples shifts toward a lower energy regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…The figure shows that the NbC nanoparticles is aggregated as a cluster at lower concentrations. When increasing the concentrations of NbC nanoparticles, the nanoparticles form a paths network inside the (PVA-PAA) blend [31]. This behavior consistent with the results of researchers [32,33].…”
Section: Introductionsupporting
confidence: 89%
“…The figure shows that the NbC nanoparticles is aggregated as a cluster at lower concentrations. When increasing the concentrations of NbC nanoparticles, the nanoparticles form a paths network inside the (PVA-PAA) blend [31]. This behavior consistent with the results of researchers [32,33].…”
Section: Introductionsupporting
confidence: 89%
“…The optical conductivity spectra indicated that the samples are transmittance within the visible and near infrared regions. Too, the optical conductivity of nanocomposites is increased with the increase of Ag nanoparticles' concentration; this behaviour is related to the creation of localized levels in the energy gap; the increase of Ag nanoparticles' concentration increases the density of localized stages in the band structure, hence, increase of the absorption coefficient consequently increasing the op-tical conductivity of (PMMA-ZrO 2 -Ag) nanocomposites [111,112].…”
Section: Resultsmentioning
confidence: 99%
“…But dielectric loss ‫)׳׳‪(ε‬‬ gain very large value (~ 6 × 10 7 ) at the low Table 3. Ionic transport number, ionic conductivity, electronic conductivity for (PEO/PAN) 20 frequency region shown in the Fig. 13.…”
Section: Dielectric Analysismentioning
confidence: 99%